A Preliminary Study of Learning Plans in SPADA LMS Based on ASSURE Model - Tutut Nani Prihatmi; Maria Istiqoma; Rini Anjarwati (Journal of Languages and Language Teaching, 2021)
This research seeks to answer to the challenge of online learning lecturers to plan their lessons more systematically by adopting ASSURE model. The change from face-to-face conventional learning to online requires more consideration and preparation, especially in learning planning. The ASSURE model is one of the instructions and learning plans that can be adopted in planning, identifying, determining goals, choosing media and material methods, and evaluating the course. The data collection technique was carried out by processing and analyzing documents from the literature, interview results, and questionnaires answered by respondents via links distributed to lecturers of the Architecture Department, Faculty of Civil Engineering and Planning, National Institute of Technology Malang. The results show that the six components of the ASSURE model of the learning planning uploaded in SPADA LMS had not been implemented optimally. Therefore, the researcher recommends for the improvement of the Semester Lesson Plan (RPS) based on the ASSURE Model to promote continuous improvements.